Medidas de segurança como meio de tratamento ao não-imputável: proposta de adequação positiva ao ordenamento penal - Souza, Renata Macedo de (2014)
Since the mankind appearance, insanity has been considered as a characteristic opposed to the social models and rules, to lead to the conclusion that someone, so called insane, is dangerous and inclined to commit crimes. Therefore, the institutionalisation of a mentally ill in a Judicial Madhouse has always been considered as a preventive treatment to guarantee social protection. During the evolution of Criminal Law, it was created an institute, known as Commitment, submitted to the existence of conditions such as occurrence of a criminal wrong, non-imputability and presumed danger, to its application. Commitment has been subjected to prolonged discussion and deliberation by Law, Criminology and Forensics Psychiatry. However, theses sciences have rarely proposed dialogues and multidisciplinary comprehension truly able to transform that institute in a worthy treatment solution to the insane. Hence, the purpose of this research is to analyse the legal conditions imposed for the application of Commitment, taking in consideration especially the presumed danger, as this institute has not always been efficient or congruent, when considered individual rights guaranties. Furthermore, this works intends also to analyse the History of the Deinstitutionalisation Movement and the influences and perspectives brought by the Act n. 10216/01, which enacts rights and guarantees for the mentally disables, to be considered by the Judiciary, when to decide about the application of Commitment